Rizikové faktory pro vznik recidivy u borderline nádorů ovaria - Líbalová, P; Vernerová, Z; Hubicková-Heringová, L; Pintérová, D; Tikovský, K; Kubecová, M; Svoboda, B (Ceska gynekologie, 2012)
OBJECTIVE: To evaluate risk factors for development of recurrent disease in borderline ovarian tumors. DESIGN: Retrospective study of 10-years single institution population. SETTING: Dept. of Gynecology and Obstetrics, 3rd Medical Faculty of Charles University in Prague. METHOD: 59 consecutive cases of borderline ovarian tumors (BOT) were analyzed for age, histopathological type, DNA ploidy, stage, presence of invasive and non-invasive peritoneal implants, type of surgical procedure, residual disease, adjuvant therapy, recurrence and long-time prognosis of the patients. RESULTS: Median follow-up was 47 months (range 1-144). There were 5 (8.5%) patients with DNA aneuploid tumors in the study group; 4 of them were younger than 50 years, 4 of them were early stage serous BOT; no one recur so far. No death of disease was described in the whole study group; only 2 patients (3.4%) developed recurrent disease - both were young patients after conservative surgery for serous diploid stage I/II BOT. Conservative surgery was the only significant factor for recurrence in univariate analysis (p = 0.0159) in our setting. CONCLUSION: DNA ploidy was not proved to be prognostic factor in borderline ovarian tumors in our study group. The only significant risk factor for development of recurrent disease was conservative surgery, with no influence on overall survival.
Keywords: senioři; DNA, Neoplasm; senioři nad 80 let; Middle Aged; Neoplasm Recurrence, Local; míra přežití; nádory vaječníků; mladý dospělý; Adult; lokální recidiva nádoru; ploidie; Aged, 80 and over; Young Adult; ženské pohlaví; Humans; Ploidies; Survival Rate; DNA nádorová; lidé středního věku; rizikové faktory; dospělí; Female; Aged; Ovarian Neoplasms; Risk Factors; lidé